(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
SSOMMARIO: 1. La riforma del processo matrimoniale nel solco del cammino sinodale della Chiesa … - 2. … e nel segno della Tradizione. Interpretazione sistematica della nuova normativa e principio dell’indissolubilità del matrimonio - 3. Le radici storiche del processus brevior: la “Episcopalis audientia” - 4. La “parabola” della “Episcopalis audientia”: contenuto e disciplina - 5. La “centralità” del Vescovo oggi come ieri - 6. La doppia sentenza conforme nell’ordinamento canonico … - 7 … e la sua evoluzione storico-giuridica: dalle origini fino al XX secolo - 8. La doppia sentenza conforme nelle Codificazioni del XX secolo - 9. La celerità dei giudizi e la pastorale della famiglia al centro della Riforma di Papa Francesco - 10. “Innovare nella tradizione: sfida e compito del canonista”. Procedural novelties regarding marriage nullity and canonical jurisdiction ABSTRACT: The purpose of the essay is to investigate the changes made to the discipline of the canonical process of marriage nullity by the Motu Proprio “Mitis Iudex Dominus Iesus”, in an attempt to verify whether the reform - which, as we know, has foreseen, among the other novelties, a shorter trial before the Bishop, and the elimination of the double sentence in conformity - both in line with the imprint proper to the canonical jurisdiction. In this perspective, the study will be dedicated to the historical reconstruction of the Processus brevior coram Episcopo and of the institute of the c.d. double sentence in conformity, at the end of which it seems possible to point out that the devolution to the Bishop of a shorter judgment - and the consequent reduction of the procedural forms - should not have undermined the cardinal principles of canonical jurisdiction.